2021
DOI: 10.22495/jgrv10i2siart10
|View full text |Cite
|
Sign up to set email alerts
|

Transforming traditional business into online: The impact of COVID-19 pandemic on consumer behavior

Abstract: COVID-19 pandemic well-known worldwide for its serious health consequences is having a profound effect on every sphere of life. Taking into consideration that COVID-19 is harming the labor market and economic activity in general, we also consider that this situation is affecting the personal consumption expenditures in case of Kosovo (Ziberi, Rexha, & Gashi, 2021). The main aim of this paper is to analyze how the customers’ behavior will shift the traditional business to an online one in case of Western Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Studies also have shown the instrumental role of technology in changing consumer avoidance purchasing behaviour (Bytyçi, Shala, Ziberi, & Myftaraj, 2021;Dong et al, 2022;Stern, Georgsson, & Carlsson, 2021). The role of technology can be further analysed to understand the aspects where it has affected the consumer behaviour at most.…”
Section: Abstract Co-occurrence Analysismentioning
confidence: 99%
“…Studies also have shown the instrumental role of technology in changing consumer avoidance purchasing behaviour (Bytyçi, Shala, Ziberi, & Myftaraj, 2021;Dong et al, 2022;Stern, Georgsson, & Carlsson, 2021). The role of technology can be further analysed to understand the aspects where it has affected the consumer behaviour at most.…”
Section: Abstract Co-occurrence Analysismentioning
confidence: 99%
“…On the customer side of business, Bytyçi et al (2021) distributed surveys to 1,250 people in Kosovo, North Macedonia and Albania. They were endeavoring to understand customers' behavior due to the Covid-19 lockdown; the results showed changes in buying behavior, with consumers shifting to online purchases.…”
Section: Logistics and Supply Chain Companies' Customer Base And Digi...mentioning
confidence: 99%
“…On the customer side of business, Bytyçi et al . (2021) distributed surveys to 1,250 people in Kosovo, North Macedonia and Albania.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Introduction 1 The coronavirus disease 2019 (COVID-19) pandemic belongs to external, unpredictable, random factors that affect all areas of life, especially economic life (Nicola, et al, 2020;Lussier, Hartmann, 2020; Jonhston, Cortez, 2020). The restrictions and lockdown introduced in Poland and many other countries forced almost all economic sectors to transfer their activities to the Internet.…”
mentioning
confidence: 99%
“…Inability and limitations of direct interpersonal contacts made it necessary to use remote forms of communication. In these conditions, enterprises, primarily commercial and service ones, were forced to serve their customers online (Pantano, et al, 2020;Bytyçi, et al, 2021). As a result, companies, institutions, and offices were forced to accelerate the digitization processes.…”
mentioning
confidence: 99%